Naturalistic Approach in Daniyal Mueenuddin’s 'Saleema' and 'In Other Rooms, Other Wonders' - Qureshi, Muhammad Farooque; Shah, Zehra; Zakir, Muhammad Mansoor (Journal of Development and Social Sciences, 2024)
In this paper, researchers intend to analyze naturalistic approach in Daniyal Mueenuddin’s short stories. He is a contemporary short story writer of Pakistan who unveils the realities of Pakistani society. His stories contain the salient features of literary naturalism. The present study qualitatively examines the naturalistic tendencies in the selected short stories, i.e., Saleema, and In Other Rooms, Other wonder. He seeks to show the conditions where characters fail to improve their social status. In present paper, Researchers explore how their survival remains difficult in their respective social and materialistic environments. Relying on the textual analysis, study has been done to determine the role of fate in the efforts of characters for their existence in society. Their dreams remain unfulfilled and ultimately they face tragic end.